(untitled) (Bangladesh Journal of Urology, 2020)
The treatment of muscle invasive bladder cancer (MIBC) is complex. This review describes the available therapies for invasive urothelial carcinoma. Neoadjuvant chemotherapy (NAC) followed by radical cystectomy (RC) and lymph node dissection has been considered the slandered treatment for MIBC. Many patients those are unfit for surgery or cisplatin ineligible, bladder sparing strategies are considered in highly selected patients. Even though there are no level I data, the treatment outcomes for highly select patients given bladder sparing therapy appear promising, with many patients retaining a functional bladder. So it can be concluded that treatment of MIBC is a multidisciplinary collaborative program of surgery, radiation and medical oncology. Bangladesh Journal of Urology, Vol. 23, No. 2, July 2020 p.205-209